Utility of Prognostic Nutritional Index and Systemic Immune‐Inflammation Index Inpatients With Sudden Sensorineural Hearing Loss: A Large Prospective Cohort Study - Xu Zhang; Junyi Wu; Wentao Zhang; Maohua Wang; Bing Guan; Qiao Jiang; Chunping Yang (Immunity, Inflammation and Disease)
ABSTRACT Background This study mainly explores the correlation between prognostic nutritional index (PNI) and systemic immune inflammatory index (SII) and sudden sensorineural hearing loss (SSNHL). Methods In this study, 150 SSNHL patients (average age 48.98 ± 16.45 years; 48.92% male, 50.93% female) were categorized into effective and ineffective treatment groups. Additionally, 150 healthy volunteers (average age 49.49 ± 9.75 years; 51.08% male, 49.07% female) served as the control group. Baseline characteristics, clinical data, and laboratory results were collected, and SII and PNI were calculated for analysis. Linear correlation, logistic regression, and receiver characteristic curve analyses were conducted to explore the link between immune nutrition levels and SSNHL. Results In the SSNHL group, PNI was significantly lower, while SII, platelet, and neutrophil counts were notably higher compared to controls (p < 0.001). Logistic regression identified low PNI (OR = 0.878), high SII (OR = 1.005), and elevated neutrophils (OR = 1.758) as predictors of SSNHL. Data comparison showed higher nutritional levels in the effective treatment group than in the ineffective group. Logistic regression indicated that low PNI (OR = 1.075) and high SII (OR = 1.004) were strongly linked to treatment outcomes. Conclusion There is a relationship between the body's immune nutrition level and the occurrence and development of SSNHL. Lower PNI and higher SII are associated with the occurrence of SSNHL and poor outcomes. However, further research into the underlying mechanisms is needed.